LegaL Position and Authority of Acting RegionaL Heads - Bakri, Riani; Jeddawi, Murtir (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2024)
The policy of simultaneously electing regional heads in 2024, both governors, regents and Mayors, has the implication that there will be many vacant regional head positions in 2022 and 2023. the essence of government in a welfare state, from protecting the community, it is also the realization of the functions of government, service and development. , regulation and empowerment, and the realization of the function not be give over eventhoght a position is vacant. the Positions are permanent and have authority, so that each position must always be filled by a permanent (definitive) or temporary position holder known as the Acting Regional Head. From philosophical analysis, theories and norms, it is concluded that permanent officials have the same legal position as temporary officials as well as the authority attached to that position. What is different is that the use of an official’s authority is strictly limited and regulated with the aim of the authority not being misused, including impartiality when there are certain contestations such as elections. With the strict use of the authority of acting regional heads, the opportunity for abuse of authority is very small. in addition, the position of an appointed official also weakens his bargaining position for inappropriate use of authority.